Analysis of Learning Model and Mathematical Material to Build Students’ Character through Mathematics Learning - Syarifah Fadillah; Dada Suhaida; Nurhayati Nurhayati; Yudi Darma (JETL (Journal of Education, Teaching and Learning), 2019)
The mathematics that has been taught from primary school to high school with a lot more time studying math in the classroom can be a passage to build students’ character. Students’ character building is not easy; therefore, it requires a planned, continuous, and systematic effort in learning mathematics. Lesson plans involving students’ character building must be purposefully designed (by design). It cannot be accidentally happened (by chance). The use of innovative learning models in learning mathematics needs to be analyzed to be able to build students’ character. This study aims to describe the relationship between learning models, mathematical material, and student character that is built through mathematics in junior high schools. This study employed a descriptive research method with a qualitative approach. Data were collected through documentation, interview, and observation techniques. Data analysis techniques followed three steps, namely data reduction, data presentation, and conclusion. The results of the analysis offered an overview of students’ character that can be formed by applying innovative learning models in learning mathematics. Furthermore, the results of the analysis will be used in developing the steps (syntax) in learning mathematics.